Polycystic ovary syndrome: the impact of diet and physical activity on the course of the disease - Urszula Ciułek; Wiktoria Bilska; Michalina Dubińska; Wiktoria Paduch-Jakubczyk; Wiktoria Zduńczyk; Ada Żydek; Anna Dobosz (Nicolaus Copernicus University in Toruń, 2024)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age, affecting between 6% and 26% of women. More than 50% of patients with polycystic ovary syndrome are obese, which contributes to the development of insulin resistance, hyperinsulinemia and other disorders of carbohydrate and lipid metabolism. These disorders in turn lead to weight gain and hormonal imbalance, creating a 'vicious circle' between the causes and effects of the disease. Therefore, preventing and treating obesity itself is extremely important in PCOS. A balanced diet and regular exercise will help to reduce fat. Adopting healthy eating habits and increasing physical activity has a positive effect on hormone management, improving fertility and reducing hirsutism or acne. It also helps to improve wellbeing and reduce symptoms of mental health problems. The most effective methods of treating and alleviating the symptoms of polycystic ovary syndrome are the implementation of a balanced diet and increased physical activity.